Membangkitkan Harapan dan Meningkatkan Resiliensi Siswa SMP - Melva Syahrial; Firman; Yarmis Syukur (CV. ITTC INDONESIA, 2024)
Adolescence is a transition period full of physical, emotional and social changes. During this period, junior high school students are faced with various challenges, such as increasingly high academic demands, social pressure from peers, and the search for identity. This can cause confusion, stress, and anxiety, which can ultimately affect student achievement. One factor that can help students face this challenge is to have hope about life. Students who have hope for life will be able to regulate emotions and behavior, and make the right decisions according to their culture. He will build healthy relationships with other people and set realistic life goals to achieve them. Established expectations help students to: develop an understanding of their values ​​and beliefs. Hope is useful for identifying what is important to them in life. Students are able to set realistic life goals and achieve them. Apart from that, it is hoped that it will increase students' resilience in facing challenges. Resilience in students will make students able to overcome pain and difficulties by becoming adaptable and resilient.